Engaging Students in Higher Education Through Mobile Learning: Lessons Learnt in a Chinese Entrepreneurship Course - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2012)
This evaluative-exploratory case study reports pedagogical experiences with using mobiles phones, wikis, and other mobile learning approaches such as podcasts and walking tours as educational tools in the context of an undergraduate course on Chinese Entrepreneurship and Asian Business Networks taught at a university in Singapore. Conceptualized as mobile learning, the paper argues that information and communication technologies (ICT) devices used by Gen Y students as part of their everyday life such as hand phones in combination with social media platforms such as course wikis and other proven pedagogical methods such as mini lectures, field visits, and walking tours can greatly enrich learners’ experience and produce valuable learning outcomes on the basis of blended learning provided their usage is easy and effectively integrated into the respective instructional strategy.